2019
DOI: 10.1007/s00397-018-01126-8
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model for the development of the morphology of disperse blends in complex flow

Abstract: The aim of this study is to develop a constitutive model for disperse blends applicable in complex flows and to cast this model in a finite element framework. As the number of droplets in realistic conditions is extremely large, it is computationally intractable to model all droplets individually. Droplet populations are modeled that have macroscopically averaged morphological properties. These properties are the droplet stretch ratio, the unstretched droplet radius, the orientation vector, and the number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Consequently, this may lead to negative values for R 0 and β, which is unphysical and makes the numerical simulations stop. We found that using the logarithmic variables v = log(R 0 ) and s = log(β) in the model and find R 0 and β by exponentiation, improved that stability of the model substantially (Wong et al 2019). With the logarithmic variables, the partial differential equations become:…”
Section: Recap Of the Previous Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, this may lead to negative values for R 0 and β, which is unphysical and makes the numerical simulations stop. We found that using the logarithmic variables v = log(R 0 ) and s = log(β) in the model and find R 0 and β by exponentiation, improved that stability of the model substantially (Wong et al 2019). With the logarithmic variables, the partial differential equations become:…”
Section: Recap Of the Previous Modelmentioning
confidence: 99%
“…In this section, we begin by summarizing the features of our previous blend morphology model (Wong et al 2019). This is followed by three extensions to our original model.…”
Section: Morphology Modelmentioning
confidence: 99%
See 3 more Smart Citations